A class of novel luminescent layered double hydroxide nanotubes. Issue 40 (15th July 2021) - Nanclares, Dimy; Morais, Alysson F.; Calaça, Thainá; Silva, Ivan G. N.; Mustafa, Danilo
Abstract : The incorporation of triply charged lanthanides in layered double hydroxides (LDHs) enables the curvature of the LDH sheets, unlocking the possibility of using a soft templating strategy to produce a class of luminescent, hierarchical LDH nanotubes. Abstract : Herein, we report a class of novel lanthanide-doped self-supported layered double hydroxide (LDH) nanotubes featuring a combination of micro- and mesoporosity. The synthesis of the nanotubes has been achieved by a soft-templating strategy. Incorporation of La 3+, Pr 3+, Nd 3+, Sm 3+, Eu 3+, Gd 3+ or Tb 3+ in the LDHs assisted the self-assembly of the double hydroxide layers onto the surface of Pluronic P-123 worm-like micelles, enabling the formation of the nanotubes. Removal of the micellar template provides accessibility to the mesopores, yielding a network of hollow cylindrical nanotubes with internal diameter of about 10 nm. An antenna molecule (benzene-1, 3, 5-tricarboxylate, BTC) is hosted in their 1-nanometre-wide micropores. Upon UV excitation, the nanotubes emit light in a set of wavelengths ranging from the ultraviolet to the infrared.